2021
DOI: 10.1177/1757913921994610
|View full text |Cite
|
Sign up to set email alerts
|

Addressing high cervical cancer rates in the Rio Grande Valley along the Texas–Mexico border: a community-based initiative focused on education, patient navigation, and medical provider training/telementoring

Abstract: Aims: Cervical cancer incidence and mortality rates are approximately 55% higher in the Rio Grande Valley (RGV) along the Texas–Mexico border compared with the average rates in the US. Our aim was to improve cervical cancer prevention efforts in the RGV through a comprehensive multilevel intervention initiative focused on community education, patient navigation, and training of local providers. Methods: We initiated a program in the RGV which consisted of (1) community education, (2) patient navigation, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Community outreach is necessary to inform uninsured women about the existence of preventative medical screenings and to link them to affordable care. Prior studies have shown that patient navigation can increase screening uptake [42][43][44]. Helping patients move through the complex healthcare system might make the process less daunting.…”
Section: Plos Onementioning
confidence: 99%
“…Community outreach is necessary to inform uninsured women about the existence of preventative medical screenings and to link them to affordable care. Prior studies have shown that patient navigation can increase screening uptake [42][43][44]. Helping patients move through the complex healthcare system might make the process less daunting.…”
Section: Plos Onementioning
confidence: 99%
“…For example, MD Anderson Cancer Center has used ECHO's telementoring approach for many years to train and support primary care providers along the Texas/Mexico border in how to screen for cervical cancer, greatly expanding access to screening for underserved Hispanic communities. 49 The ECHO Cancer Network has allowed local providers to triage complex patients to MD Anderson when expert care is required, using the linkages created by this mentorship network to reduce the time to treatment for those who need complex care that only specialists can provide. [50][51][52] Most ECHO oncology partner organizations rely on the generosity of philanthropy or short-term federal grants to operate and expand these networks.…”
Section: Health Policy Implicationsmentioning
confidence: 99%
“…An average of 8.6% of the US population is uninsured, although the rates are much higher in certain states, such as Texas, where 18.4% of the population is uninsured 20,21. Additional barriers to treatment of cervical preinvasive disease include lack of patient awareness and lack of patient knowledge,19,22 lack of adequate system infrastructure to identify and navigate patients in need of treatment, lack of clinical infrastructure to perform diagnostic and treatment procedures, as well as regional lack of trained professionals delivering these services 23–25…”
mentioning
confidence: 99%
“…20,21 Additional barriers to treatment of cervical preinvasive disease include lack of patient awareness and lack of patient knowledge, 19,22 lack of adequate system infrastructure to identify and navigate patients in need of treatment, lack of clinical infrastructure to perform diagnostic and treatment procedures, as well as regional lack of trained professionals delivering these services. [23][24][25] In 2018, Dr Tedros Adhanom Ghebreyesus, Director General of the World Health Organization (WHO), released a call for action to eliminate cervical cancer worldwide, and in 2020 this call for action was adopted as the global strategy for cervical cancer elimination by the World Health Assembly. 26 The aspirational goal of this initiative is to eliminate cervical cancer as a public health problem by 2030 through implementing initiatives to achieve 3 targets: (1) vaccinate 90% of girls with the HPV vaccine; (2) screen 70% of women for cervical cancer using a highperformance test; and (3) treat 90% of women with cervical precancer and cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation